'Then her neighbour will not know her status': how health providers advocate antiretroviral therapy under universal test and treat. Issue 1 (18th August 2018) - Pell, Christopher; Reis, Ria; Dlamini, Njabuliso; Moyer, Eileen; Vernooij, Eva
Abstract: Introduction: Universal test and treat (UTT)—antiretroviral therapy (ART) for all HIV-positive individuals regardless of CD4 count—is the WHO's recommended treatment guideline. UTT has implications for health providers' workload in areas of high HIV prevalence and for understandings of ART and HIV. This article explores health providers' experiences of implementing UTT in Hhohho Region, Eswatini. Methods: Between March 2015 and October 2016, in-depth interviews were conducted with health providers implementing UTT. Interviews were transcribed verbatim and translated into English for qualitative content analysis. Results: Twenty-five providers from eight facilities were interviewed. Respondents encouraged early ART by promoting its overall health benefits, and the possibility of avoiding disclosure and HIV-related stigma in the community. Some health providers downplayed UTT's preventive benefits to avoid discouraging condom use. Respondents suggested that initiating ART immediately after testing could improve linkage-to-care, but recognized that overly hasty initiation might affect adherence. Viral load testing was seen as a potentially useful tool to monitor clients' response to ART. Conclusions: Health providers appropriated stigma to encourage early ART. This suggests an attentiveness to the social burden of HIV/AIDS, but potentially exacerbates discrimination and conflicts with efforts to reduce HIV-related stigma.